Quality of life, treatment satisfaction, and adherence to treatment in patients with vesicular hand eczema: a cross-sectional study - Politiek, Klaziena; Ofenloch, Robert (Contact dermatitis, 2020)
Background Recurrent vesicular hand eczema frequently has a chronic course and needs long-term treatment. Objectives To evaluate health-related quality of life (HRQoL), treatment satisfaction, and adherence in patients with vesicular hand eczema. Methods Patients using one main treatment for at least three months were included. Data on HRQoL (Quality of Life in Hand Eczema Questionnaire [QOLHEQ]), treatment satisfaction (Treatment Satisfaction Questionnaire for Medication, version II), and treatment adherence (4-item Morisky Medication Adherence Scale) were collected. Univariate and multivariate regression analysis were used to predict variables associated with HRQoL. Results HRQoL was moderately impaired, with the highest impact in the QOLHEQ subdomain symptoms. Female sex, more severe hand eczema, and lower treatment satisfaction were associated with more impairment in HRQoL. Patients with severe/very severe hand eczema had significant lower “global satisfaction” scores compared with the other severity groups. The “global satisfaction” and treatment adherence in patients using systemic treatment were significantly higher compared with those with only topical treatment. Conclusions In patients with vesicular hand eczema disease severity affects both HRQoL and treatment satisfaction. Systemic treatment of severe hand eczema could improve the severity and as a result also HRQoL, treatment satisfaction, and medication adherence.